Description of dynamic shared knowledge: an exploratory study during a competitive team sports interaction - Bourbousson, J.; Poizat, G.; Saury, J.; Seve, C. (Ergonomics, 2011)
This exploratory case study describes the sharedness of knowledge within a basketball team (nine players) and how it changes during an official match. To determine how knowledge is mobilised in an actual game situation, the data were collected and processed following course-of-action theory (Theureau 2003). The results were used to characterise the contents of the shared knowledge (i.e. regarding teammate characteristics, team functioning, opponent characteristics, opposing team functioning and game conditions) and to identify the characteristic types of change: (a) the reinforcement of a previous element of shared knowledge; (b) the invalidation of an element of shared knowledge; (c) fragmentation of an element of shared knowledge; (d) the creation of a new element of shared knowledge. The discussion deals with the diverse types of change in shared knowledge and the heterogeneous and dynamic nature of common ground within the team.